Treatment of traumatic brain injury with thymosin β4 in rats - Xiong, Ye (2010)
OBJECT: This study was designed to investigate the efficacy of delayed thymosin β(4) (TB4) treatment of traumatic brain injury (TBI) in rats. METHODS: Young adult male Wistar rats were divided into the following groups: 1) Sham group (6 rats); 2) TBI + Saline group (9 rats); 3) and TBI + Tβ(4) group (10 rats). TBI was induced by controlled cortical impact over the left parietal cortex. Thymosin β(4) (6 mg/kg) or saline was administered intraperitoneally starting at Day 1 and then every 3 days for an additional 4 doses. Neurological function was assessed using a modified neurological severity score (mNSS), footfault and Morris water maze tests. Animals were killed 35 days after injury, and brain sections stained for immunohistochemistry to assess angiogenesis, neurogenesis, and oligodendrogenesis after Tβ(4) treatment. RESULTS: Compared to the saline treatment, delayed Tβ(4) treatment did not affect lesion volume but significantly reduced hippocampal cell loss, enhanced angiogenesis and neurogenesis in the injured cortex and hippocampus, increased oligodendrogenesis in the CA3 region, and significantly improved sensorimotor functional recovery and spatial learning. CONCLUSIONS: These data for the first time demonstrate that delayed administration of Tβ(4) significantly improves histological and functional outcomes in rats with TBI, indicating that Tβ(4) has considerable therapeutic potential for patients with TBI.